Excess total mortality during the Covid-19 pandemic in Italy: updated estimates indicate persistent excess in recent months - Alicandro, Gianfranco; Remuzzi, Giuseppe; Centanni, Stefano; Gerli, Alberto; La Vecchia, Carlo (La Medicina del Lavoro, 2022)
Background: New releases of daily mortality data are available in Italy; the last containing data up to 31 January 2022. This study revises previous estimates of the excess mortality in Italy during the Covid-19 pandemic. Methods: Excess mortality was estimated as the difference between the number of registered deaths and the expected deaths. Expected deaths in March-December 2020, January-December 2021 and January 2022 were estimated separately by sex, through an over-dispersed Poisson regression model using mortality and population data for the period 2011-2019. The models included terms for calendar year, age group, a smooth function of week of the year and the natural logarithm of the population as offset term. Results: We estimated 99,334 excess deaths (+18.8%) between March and December 2020, 61,808 deaths (+9.5%) in 2021 and 4143 deaths (+6.1%) in January 2022. Over the whole pandemic period, 13,039 excess deaths (+10.2%) were estimated in the age group 25-64 years with most of the excess observed among men [10,025 deaths (+12.6%) among men and 3014 deaths (+6.3%) among women]. Conclusions: Up to 31 January 2022, over 165 thousand excess deaths were estimated in Italy, of these about 8% occurred among the working age population. Despite high vaccination uptake, excess mortality is still observed in recent months.